Morbus Parkinson - Wüllner, Ullrich; Kalenka, Armin (Der Anaesthesist, 2012)
Approximately 10,000-15,000 Parkinson’s disease (PD) patients per year undergo surgery in Germany. The demographic developments along with further surgical progress and procedural refinements will lead to increasing numbers of PD patients in the operating theatre (OR). There are several perioperative risk factors for PD patients, they more often require prolonged intensive care treatment and warrant particular anesthesiological attention with regard to the choice of drugs and equipment. Careful evaluation of concomitant diseases, maintenance of oral Parkinson therapeutic drugs up to the time of surgery and continuous perioperative dopaminergic therapy are key factors for reducing postoperative morbidity in PD patients undergoing surgery.